An Information Operational Model for the Goods Maritime Transport Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The research aimed to develop and to assess an information operational model for the goods maritime transport management in Thai supply chain A samples are ten experts in the field of information. and supply chain. The data is analysed by means and standardized deviations. The research about an information operational model for the goods maritime transport management in Thai supply chain consists of six elements namely main elements Carriers , Port operator, Freight forwarders Suppliers and Customers. The assessment about an information operational model for the goods maritime transport management in Thai supply chain using Black-Box technique. The research findings revealed that an information operational model for the goods maritime transport management in Thai supply chain is appropriate at the high level which mean that This model can be develop information system.